Exploring scale in social licence to operate: European perspectives. (15th January 2023) - Lesser, Pamela; Poelzer, Gregory; Gugerell, Katharina; Tost, Michael; Franks, Daniel
Abstract: This article explores the issue of scale in the social licence to operate (SLO) which, to date, is understudied. The community-company relationship is the original, and still predominant, conceptualization of the term with the less tangible society-industry relationship still not typically in focus. Although the literature distinguishes between community and societal scales, there is no research on why the distinction is important, how the two scales are integrated or whether they interact with and influence one another. Exploring scale in SLO is important for theoretical clarification of the concept, for better empirical understanding of the role mining plays in host localities and the broader society and for the potential to incentivize industry toward more responsible and sustainable practices. Europe's multi-layered governance structure combined with its push for more domestic mining activities provides an ideal crucible for debates of scale to play out. To investigate the community and societal scales in the European context within a single study, three main research questions guide the work: how do orientations toward SLO differ at the community and societal scales; how do these orientations influence the acceptance of mining at both scales; and how do these orientations interact and influence one another? Through quantitative analyses, we found that site level factors tend to be important predictors for local communities and more distant society, but broader societal benefits and costs are not important predictors at the local community scale, and are only significant at the societal scale in combination with local factors. Highlights: Orientations toward SLO differ at the community and societal scales. Site level factors tend to be important predictors for local communities and more distant society. Broader societal benefits and costs are not important predictors at the local community scale. Broader societal benefits are only significant at the societal scale in combination with local factors.